Fast-type sporadic Na and K layers over São José dos campos, Brazil, and their link to meteor ablation - Andrioli, Vania F.; Xu, Jiyao; Batista, Paulo P.; Resende, Laysa C. A.; Santos, Angela M.; Olajide-Owoyomi, Femi; Pimenta, Alexandre A.; Martins, Maria P. P.; Da Silva, Ligia A.; Moro, Juliano; de Jesus, Rodolfo; Yang, Guotao; et al. (Frontiers in Astronomy and Space Sciences, 2025)
This study utilizes 3 years of observational data from the China-Brazil Joint Laboratory for Space Weather (CBJLSW) dual-beam Na-K LIDAR to investigate fast-type sporadic sodium (Na) and potassium (K) layers. The focus is on the sudden enhancement of these metal densities within thin layers, the duration of which is less than 1 hour. These transient layers were identified in five nights of observational data and were always located a few hundred meters above the main Na and K layers. There was a good correspondence between the fast-type Ns layer and the occurrence of the Sporadic-E (Es) layer, which also presented a short time of duration. Moreover, the results show an increase in the meteor rate during these Ns layers’ time and altitudinal range. Our analysis aims to elucidate the formation mechanisms of these fast-type neutral sporadic layers. The slightly higher peak altitudes and earlier started time observed in the Na layer compared to K are evidence of the link to differential meteor ablation. Additionally, the different values found in the relative abundance of the Na to K ratio between the Ns and background layers indicate an extra input of metals in the layers instead of a vertical redistribution of the pre-existing metal normal layer. The findings suggest that the formation of the fast-type Ns layers is linked to the direct deposition of these metals by meteor ablation.